Socio-Economic Theoretical Framework of Women Entrepreneurship Development in Bangladesh (Global Journal of Management and Business Research, 2015)
The paper aims to analyze the Socio-economic factors of Women Entrepreneurship Development in Bangladesh. The analysis is based on recent theoretical ideas that have been supported by empirical research findings conducted by the renowned academic researchers. The paper depicts a Socio-economic Framework of Women Entrepreneurship Development based on Institutional Theory, which focuses on three factors: Regulative, Normative, and Cognitive. Regulative factors refer to different rules and regulations of the Government that facilitate Women Entrepreneurship Development in Bangladesh. Normative and Cognitive factors include norms, rules, regulation, and values of society. Based on the analysis of these factors, the paper provides many significant policy implications on how to improve women entrepreneurship development in Bangladesh.
Keywords: socio-economic; social stigma; cognitive; bwcci; SMES; CEDAW